Blood Biomarkers and Structural Imaging Correlations Post-Traumatic Brain Injury: A Systematic Review. Issue 2 (13th February 2022) - Whitehouse, Daniel P.; Vile, Alexander R.; Adatia, Krishma; Herlekar, Rahul; Roy, Akangsha Sur; Mondello, Stefania; Czeiter, Endre; Amrein, Krisztina; Büki, András; Maas, Andrew I. R.; Menon, David K.; Newcombe, Virginia F. J.
Abstract : BACKGROUND: Blood biomarkers are of increasing importance in the diagnosis and assessment of traumatic brain injury (TBI). However, the relationship between them and lesions seen on imaging remains unclear. OBJECTIVE: To perform a systematic review of the relationship between blood biomarkers and intracranial lesion types, intracranial lesion injury patterns, volume/number of intracranial lesions, and imaging classification systems. METHODS: We searched Medical Literature Analysis and Retrieval System Online, Excerpta Medica dataBASE, and Cumulative Index to Nursing and Allied Health Literature from inception to May 2021, and the references of included studies were also screened. Heterogeneity in study design, biomarker types, imaging modalities, and analyses inhibited quantitative analysis, with a qualitative synthesis presented. RESULTS: Fifty-nine papers were included assessing one or more biomarker to imaging comparisons per paper: 30 assessed imaging classifications or injury patterns, 28 assessed lesion type, and 11 assessed lesion volume or number. Biomarker concentrations were associated with the burden of brain injury, as assessed by increasing intracranial lesion volume, increasing numbers of traumatic intracranial lesions, and positive correlations with imaging classification scores. There were inconsistent findings associating different biomarkers with specific imaging phenotypes including diffuse axonal injury, cerebral edema, and intracranial hemorrhage. CONCLUSION: Blood-based biomarker concentrations after TBI are consistently demonstrated to correlate burden of intracranial disease. The relation with specific injury types is unclear suggesting a lack of diagnostic specificity and/or is the result of the complex and heterogeneous nature of TBI. Abstract :